Inhibition of transcription-regulating properties of nonstructural protein 1 (NS1) of parvovirus minute virus of mice by a dominant-negative mutant form of NS1 - Deleu, Laurent; Nüesch, Jürg P. F.; Rommelaere, Jean (Journal of general virology, 2001)
Nonstructural protein 1 (NS1) of minute virus of mice is involved in viral DNA replication, transcriptional regulation and cytotoxic action in the host cell. Viral DNA replication is dependent on the ability of NS1 to form homo-oligomers. To investigate whether oligomerization is required for NS1 transcriptional activities, a functionally impaired mutant derivative of NS1 that was able to interact with the wild-type (wt) protein and inhibit its activity in a dominant-negative manner was designed. This mutant provided evidence that transactivation of the parvoviral P38 promoter and transinhibition of a heterologous promoter by NS1 were both affected by the co-expression of the wt and the dominant-negative mutant form of NS1. These results indicate that additional functions of NS1, involved in promoter regulation, require oligomer formation.,
Gesehen am 15.02.2021